Entropy and enumeration of Boolean functions - Pippenger, H. (IEEE transactions on information theory, 1999)
Shannon's notion of the entropy of a random variable is used to give simplified proofs of asymptotic formulas for the logarithms of the numbers of monotone Boolean functions and Horn (1951) functions, and for equivalent results concerning families of sets and closure operations.